South American Guidelines for Cardiovascular Disease Prevention and Rehabilitation - Herdy,AH (2014)
In this document, the Inter-American Committee of Cardiovascular Prevention and Rehabilitation, together with the South American Society of Cardiology, aimed to formulate strategies, measures, and actions for cardiovascular disease prevention and rehabilitation (CVDPR). In the context of the implementation of a regional and national health policy in Latin American countries, the goal is to promote cardiovascular health and thereby decrease morbidity and mortality. The study group on Cardiopulmonary and Metabolic Rehabilitation from the Department of Exercise, Ergometry, and Cardiovascular Rehabilitation of the Brazilian Society of Cardiology has created a committee of experts to review the Portuguese version of the guideline and adapt it to the national reality. The mission of this document is to help health professionals to adopt effective measures of CVDPR in the routine clinical practice. The publication of this document and its broad implementation will contribute to the goal of the World Health Organization (WHO), which is the reduction of worldwide cardiovascular mortality by 25% until 2025. The study group's priorities are the following: • Emphasize the important role of CVDPR as an instrument of secondary prevention with significant impact on cardiovascular morbidity and mortality; • Join efforts for the knowledge on CVDPR, its dissemination, and adoption in most cardiovascular centers and institutes in South America, prioritizing the adoption of cardiovascular prevention methods that are comprehensive, practical, simple and which have a good cost/benefit ratio; • Improve the education of health professionals and patients with education programs on the importance of CVDPR services, which are directly targeted at the health system, clinical staff, patients, and community leaders, with the aim of decreasing the barriers to CVDPR implementation.